Christ and Modernity : Christian Self-Understanding in a Technological Age. - Hawkin, David J. (Wilfrid Laurier University Press, 2006)
In this re-examination of the roots of the relationship between religion and science, David Hawkin focuses on the concept of autonomy as he explores the question: Is there continuity and compatibility between the autonomy that underlies Christian faith and the role of individual freedom in the technological age? What makes this work particularly valuable is Professor Hawkin's review of the theological, philosophical, political, psychological, and sociological works that have formed our ideas of the nature of both Christianity and modernity - Reimarus, Strauss, Schweitzer, and Bult.